2017
DOI: 10.1073/pnas.1703438114
|View full text |Cite
|
Sign up to set email alerts
|

Anterior temporal lobe and the representation of knowledge about people

Abstract: Patients with semantic dementia (SD), a neurodegenerative disease affecting the anterior temporal lobes (ATL) (1), present with striking cognitive deficits: they can have difficulties naming objects and familiar people from both pictures and descriptions (2, 3). Furthermore, SD patients make semantic errors (e.g., naming "horse" a picture of a zebra), suggesting that their impairment affects object knowledge rather than lexical retrieval. Because SD can affect object categories as disparate as artifacts, anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Consistent with the idea that the ATL supports the integration of online and offline social processes, different lines of research have demonstrated the convergence of multimodal, social information processing streams in the anterior portions of the temporal lobe. Ventral areas of the ATL are involved in the encoding and retrieval of person-specific knowledge (e.g., name and biographical information; 16,21,54,55), while more dorsal, anterior portions of the ATL are considered a semantic hub for abstract social knowledge (14,18,(56)(57)(58)(59)(60). Our findings span the middle ground between the aforementioned lines of research, such that our findings suggest an integration of person-specific and abstract social knowledge representations.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Consistent with the idea that the ATL supports the integration of online and offline social processes, different lines of research have demonstrated the convergence of multimodal, social information processing streams in the anterior portions of the temporal lobe. Ventral areas of the ATL are involved in the encoding and retrieval of person-specific knowledge (e.g., name and biographical information; 16,21,54,55), while more dorsal, anterior portions of the ATL are considered a semantic hub for abstract social knowledge (14,18,(56)(57)(58)(59)(60). Our findings span the middle ground between the aforementioned lines of research, such that our findings suggest an integration of person-specific and abstract social knowledge representations.…”
Section: Discussionsupporting
confidence: 55%
“…However, these regions are also associated with other functions that may play a role in social interaction. For example, the ATL and STS are also associated with the representation of person-specific information (14)(15)(16)(17)(18)(19)(20)(21), while the IFG has been implicated in a range of executive processes, such as working memory and behavioral inhibition (22)(23)(24). Thus, it is unclear if the overlapping activity associated with social interaction reported by Alkire et al (11) is specific to mentalizing or reflects other higher-order cognitive processes.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the idea that the ATL supports the integration of online and offline social processes, different lines of research have demonstrated the convergence of multimodal, social information processing streams in the anterior portions of the temporal lobe. Ventral areas of the ATL have been associated with the representations of person‐specific knowledge (e.g., names, faces, and biographical information; Anzellotti, 2017 ; Blank et al, 2015 ; Borghesani et al, 2019 ; Kriegeskorte et al, 2007 ; Wang et al, 2017 ), while more dorsal, anterior portions of the ATL are considered to be a semantic hub for abstract social concepts (including mental‐state concepts; Arioli et al, 2020 ; Olson et al, 2007 , 2013 ; Skipper et al, 2011 ; Wang et al, 2019 ; Zahn et al, 2007 ). Conceptually, our findings span the middle ground between the aforementioned lines of research in that our results suggest that peer‐specific and abstract knowledge about mental states are integrated and represented similarly in the ATL.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Alkire et al ( 2018 ) reported overlapping activations in the ATL, STS, and IFG when children reasoned about the mental state of an abstract character and when they engaged in social interactions that did not explicitly require mental state reasoning, and inferred that social interaction may induce spontaneous mentalizing. However, these brain regions are associated with other, higher‐order cognitive processes that may be important for social interactions—the ATL and STS are associated with the representation of person‐specific information (Anzellotti, 2017 ; Anzellotti & Caramazza, 2017 ; Blank et al, 2015 ; Collins et al, 2016 ; Olson et al, 2013 ; Perrodin et al, 2015 ; Simmons et al, 2010 ; Wang et al, 2017 ), and the IFG is implicated in a range of executive processes, such as working memory and behavioral inhibition (Breitling et al, 2020 ; Drummond et al, 2017 ; Hartwigsen et al, 2019 ). Thus, it is unclear if the overlapping activity associated with social interaction reported by Alkire et al ( 2018 ) is specific to mentalizing, or reflects other cognitive processes utilized within social interactive contexts.…”
Section: Second‐person Neurosciencementioning
confidence: 99%
“…For example, regions considered to be outside the core face networks, such as different extrastriate visual areas, the structures in the anterior and medial temporal lobe (MTL) have been reliably demonstrated to exhibit stronger responses to familiar stimuli, including faces. The anterior temporal lobe (ATL), considered to be a semantic hub (Anzellotti, 2017), is involved in associations of person-related semantics (Morton et al, 2021), e.g. a connection between a name and a face (Tsukiura et al, 2010).…”
Section: Discussionmentioning
confidence: 99%